Gustatory Function in Patients With Chronic Rhinosinusitis. (April 2018) - Wolf, Axel; Renner, Bertold; Tomazic, Peter V.; Mueller, Christian A.
Objectives: Recent research has shown that taste receptors in airway epithelial cells are involved in defending against upper respiratory tract infection. The aim of the present study was to investigate gustatory function in patients with chronic rhinosinusitis (CRS). Methods: Taste function was assessed using the extended "taste strip" test in 37 patients with CRS (20 males, 17 females; mean age = 32.1 years; range, 20-82 years) and 135 healthy controls (70 males, 65 females; mean age = 29.5 years; range, 18-84 years). Results: The mean (±SD) total extended taste score was 12.8 (±3.5) in patients and 14.5 (±3.2) in controls. Analysis of variance indicated an interaction of sinusitis and gender ( P < .05) with significantly lower total scores and significantly poorer results for the bitter taste among male patients compared to controls ( P < .01). In addition, CRS patients exhibited a trend toward decreased sweet taste perception compared to controls, but this did not reach significance ( P = .051). Conclusions: Patients with CRS exhibited decreased gustatory function compared to healthy controls. The effect was most pronounced for bitter taste. Thus, the assessment of gustatory function seems to be useful for detecting potential risk factors for recurrent upper respiratory tract infection.